AB0087 Takayasu's arteritis: review and four clinical cases. (1st June 2001) - Sequeira, G; Saraiva, F; Marques, A; Romeu, J; Costa, T; Queiroz, V
Abstract : Background: Takayasu's arteritis is a rare disease, mainly affecting young women. The authors describe four cases of Takayasu's disease from the rheumatology outpatient clinic of Hospital de Santa Maria in Portugal. A revision of the disease is made concerning it's clinical manifestations, laboratory, diagnosis, treatment and prognosis. Objectives: Methods: Results: All patients were female, three were white and one black. Begining of symptoms was between 7 and 56 years, satisfying the American College of Rheumatology criteria for the classification of Takayasu's arteritis. The spectrum of presentation, disease activity and pace of disease progression were very variable. The delay between the onset of first symptoms and diagnosis was less than three years in three patients and twenty in the other. The first symptoms of disease were in two patients systemic reactions such as malaise, fever and anorexia, absent pulses in the lower limbs in another and claudication of the upper extremities in the last. Vascular ischaemic symptoms, hallmark of the disease, were present in the four patients and all of them had angiograms that involved visualisation of at least primary tributaries that showed lesions of the aortic arch and its branches. All patients needed corticosteroid treatment in the acute inflammatory phase of the disease. Cytotoxic agents were used in three of them and in two cases vascular surgery was done because of fear of occlusion of the involved vessels. Conclusion: Females and caucasian race predominated. The diagnosis of Takayasu's arteritis should be considered in the presence of symptoms of vascular ischemia such as pulse defects or signs of bruits and in the angiografic study. The prominence of inflammatory features antedating obvious symptoms often delayed diagnosis for substantial periods of time. Fever, myalgia/arthralgia with no identified cause, elevated erythrocyte sedimentation rate, claudication, diminished or absent pulses, bruits, vascular pain and the typical angiographic features are criteria for disease activity. The mainstay of treatment is oral corticosteroids. They are very effective in controlling clinical manifestations and arresting disease progression and sometimes in achieving return of previously absent pulses. Cytotoxic therapy has been helpful in patients failing to respond to corticosteroids.